Description of the pupa of Climaciella brunnea (Say) (Mantispidae, Mantispinae) and a key to known pupae of mantispids from North America - Marquez-López, Yesenia; Contreras-Ramos, Atilano (Zootaxa, 2018)
Most works about Climaciella brunnea (Say) deal with predation and parasitoidism on wolf spiders (Lycosidae), or records of populations that mimic vespid wasps (Polistes spp.). Knowledge on immature mantispids is scarce, particularly about pupae. Currently, a key by Hoffman and Brushwein provides information on larvae and pupae of several North American species. Herein, the pupa of C. brunnea is described for the first time, on the basis of a specimen from central Mexico, and its position in the available key is proposed,. The pupa of Plega yucatanae Parker & Stange from southeastern Mexico is also incorporated to the key on the basis of a published description.